The implementation of Coaching for Prisoners of Drug Abuse Narcotics as a Preventive Effort Narcotics Crime (Case Study of Class II Langkat Narcotics Correctional Institution) - Rudi Prasetyo Panjaitan; T. Riza. Zarzani (LAWYER: Jurnal Hukum, 2023)
Guidance is provided to drug inmates in an attempt to prevent recidivism (case study at Langkat Type 2 Drug Correctional Facility). The purpose of this study was to examine the implementation status of the guidance provided by Class II Langkat Narcotics Correctional Facility to drug-abusing inmates to prevent relapse to criminal behavior, and the implementation of inmate guidance at Langkat Narcotics Correctional Facility. It is to judge the effectiveness of Class II is to be determined. The test was conducted at Class II Langkat Narcotics Prison. The data obtained were processed and analyzed descriptively and qualitatively. This involves collecting, compiling, interpreting, and analyzing data to provide a complete explanation according to the problem at hand. The results showed that (1) the implementation of class II run cut narcotic instruction in correctional facilities is carried out at several stages, including the initial stage, advanced stage, and terminal stage; In the early stages include personality development and independence, in the advanced stage there is an assimilation stage where the inmate is entitled to leave before release or parole. at this stage also implemented social work assimilation which aims that if the inmate later has been released then he is not ostracized by the community and does not repeat the crime again. This final stage of coaching will be given parole for prisoners who have met the requirements. (2) The implementation of inmate coaching at the Class II Langkat Narcotics Penitentiary has been going well but has not been able to run effectively. This is because the implementation of coaching is not classified based on the crime, which means that the coaching carried out on narcotics and non-narcotics prisoners is equalized.